Genetic predisposition for ovarian cancer development - Joksić, Ivana; Prosenc Zmrzljak, Uršula; Ninić, Ana; Ratković, Tamara; Munjas, Jelena (Archives of Pharmacy, 2025)
Ovarian cancer is a leading malignancy in the female reproductive system and is responsible for more deaths than any other type of cancer affecting this system. Ovarian cancers can be hereditary or sporadic. Anatomic, cellular, microenvironmental and molecular features of ovarian cancers show a high degree of heterogeneity. Numerous genes implicated in the pathogenesis and progression of ovarian cancers have been identified to date. The majority of these genes act as tumour suppressor genes, oncogenes, or are involved in mismatch repair and double-strand break repair mechanisms. The identification of mutations in cancer susceptibility genes could be a major step forward towards earlier diagnosis, personalized therapy approaches and outcome monitoring. In healthy women, detecting a specific mutated gene can provide a rationale for personalized surveillance, chemopreventive strategies, and prophylactic surgery. Next-generation sequencing offers comprehensive genome analysis, which enables profound understanding and identification of cancer susceptibility genes, and new molecular diagnostic markers and therapeutic targets.